2011
DOI: 10.13005/bbra/862
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO and Rh Blood Groups with the Carcinoma of the Cervix with Special Reference to Jammu Region

Abstract: AimThe present study was designed to investigate the association of ABO blood group types in cervical cancer. Material and MethodsThe study sample consisted of 248 subjects as confirmed cases of cervical cancer and 254 individuals as controls. Data about the blood group types was collected from the blood bank of Govt. Medical College, Jammu. ResultsA statistical significant difference in the distribution of ABO blood groups between the patients and controls was observed. The incidence of B-type group was the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…14 A higher risk of carcinoma cervix was found in group B (42.3%) in the present study, which is similar to many other studies findings who also reported a higher incidence of carcinoma cervix ,genitourinary cancers with blood group B. 15,16 Also, a significant association was observed between carcinoma ovary and individuals with blood group A (32.8%), which is again similar to findings of other research groups who showed that in comparison to O group , blood group A was significantly more common with ovarian cancer. [15][16][17] There were certain limitations of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…14 A higher risk of carcinoma cervix was found in group B (42.3%) in the present study, which is similar to many other studies findings who also reported a higher incidence of carcinoma cervix ,genitourinary cancers with blood group B. 15,16 Also, a significant association was observed between carcinoma ovary and individuals with blood group A (32.8%), which is again similar to findings of other research groups who showed that in comparison to O group , blood group A was significantly more common with ovarian cancer. [15][16][17] There were certain limitations of this study.…”
Section: Discussionsupporting
confidence: 91%
“…15,16 Also, a significant association was observed between carcinoma ovary and individuals with blood group A (32.8%), which is again similar to findings of other research groups who showed that in comparison to O group , blood group A was significantly more common with ovarian cancer. [15][16][17] There were certain limitations of this study. The studied population was limited to only those who had attended the blood bank for blood requisition.…”
Section: Discussionsupporting
confidence: 84%
“…Study on the association between blood groups and several diseases has been carried out by various workers [6][7][8][9][10][11][12][13][14] . There are only a few studies available regarding the relationship of ABO blood groups and risk of developing ovarian malignancies and these studies have stated contradictory results [12,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Since 1953, the relationship of ABO blood groups with incidence, clinicopathologic characteristics, and prognosis of many diseases has been established [7] . Some recent studies have shown the association of ABO blood groups with cancer of the cervix [8] , oral premalignancies [9] , cancer mortality [10] and breast cancer [11] . Several plausible mechanisms, including inflammation, immune-surveillance for malignant cells, intercellular adhesion, and membrane signalling have been proposed to explain the observed association between ABO blood groups and cancer risk [4] .…”
Section: Introduction:-mentioning
confidence: 99%
“…Different biological factors such as molecular and gene associations and hormonal balance can predispose to breast cancer and play a role in malignancy development. Cervix cancer is second the most common cancer in females that mainly occurs in developing countries 2 . Studies show that control and prevention are crucial for this deadly cancer 3 .…”
Section: Introductionmentioning
confidence: 99%